Anodic electrochemical performances of MgCo2O4 synthesized by oxalate decomposition method and electrospinning technique for Li-ion battery application. (January 2016) - Darbar, Devendrasinh; Reddy, M.V.; Sundarrajan, S.; Pattabiraman, R.; Ramakrishna, S.; Chowdari, B.V.R.
Graphical abstract: Highlights: MgCo2 O4 was prepared by oxalate decomposition method and electrospinning technique. Electrospun MgCo2 O4 shows the reversible capacity of 795 and 227 mAh g −1 oxalate decomposition MgCo2 O4 after 50 cycle. Electrospun MgCo2 O4 show good cycling stability and electrochemical performance. Abstract: Magnesium cobalt oxide, MgCo2 O4 was synthesized by oxalate decomposition method and electrospinning technique. The electrochemical performances, structures, phase formation and morphology of MgCo2 O4 synthesized by both the methods are compared. Scanning electron microscope (SEM) studies show spherical and fiber type morphology, respectively for the oxalate decomposition and electrospinning method. The electrospun nanofibers of MgCo2 O4 calcined at 650 °C, showed a very good reversible capacity of 795 mAh g −1 after 50 cycles when compared to bulk material capacity of 227 mAh g −1 at current rate of 60 mA g −1 . MgCo2 O4 nanofiber showed a reversible capacity of 411 mAh g −1 (at cycle) at current density of 240 mA g −1 . Improved performance was due to improved conductivity of MgO, which may act as buffer layer leading to improved cycling stability. The cyclic voltammetry studies at scan rate of 0.058 mV/s show main cathodic at around 1.0 V and anodic peaks at 2.1 V vs. Li.